Bridging and bonding interactions in higher education: social capital and students’ academic and professional identity formation - Jensen, Dorthe H.; Jetten, Jolanda (Frontiers in Psychology, 2015)
It is increasingly recognized that graduates’ achievements depend in important ways on their opportunities to develop an academic and a professional identity during their studies. Previous research has shown that students’ socio-economic status and social capital prior to entering university affects their ability to obtain these identities in higher education. However, what is less well understood is whether social capital that is built during university studies shapes identity development, and if so, whether the social capital gained during university years impacts on academic and professional identity differently. In a qualitative study, we interviewed 26 Danish and 11 Australian university students about their social interaction experiences, their opportunities to develop bonding capital as well as bridging capital, and their academic and professional identity. Findings show that while bonding social capital with co-students facilitated academic identity formation, such social capital does not lead to professional identity development. We also found that the development of bridging social capital with educators facilitated students’ professional identity formation. However, bonding social capital among students stood in the way of participating in bridging interaction with educators, thereby further hindering professional identity formation. Finally, while students’ parental background did not affect the perceived difficulty of forming professional identity, there was a tendency for students from lower SES backgrounds to be more likely to make internal attributions while those from higher SES backgrounds were more likely to make external attributions for the failure to develop professional identity. Results point to the importance of creating opportunities for social interaction with educators at university because this facilitates the generation of bridging social capital, which, in turn, is essential for students’ professional identity development.